Bacteriocin from Streptococcus salivarius optimized statistically by response surface methodology active against different clinical oral pathogenic Streptococci - AL-Saeedi, Bayan Shakir Mahmood; Luti, Khalid Jaber Kadhum (Iraqi Journal of Science, 2018)
The aim of the present work was to study the possibility of producing an effective bacteriocin from bacteria naturally exists in the mouth. Streptococcus salivarius KA101 was selected among 120 oral isolates collected from healthy people based on its ability to produce an effective bactericidal bacteriocin. Modified tryptic soy agar with 2% yeast extract and 0.1% calcium carbonate was the best medium for the production of bacteriocin with an activity of 40 AU/ml. Response surface methodology (RSM) based on central composite design (CCD) was employed to build a model in order to evaluate the optimum effective factors for bacteriocin production using four factors: yeast extract, CaCO3, pH and incubation time. Based on the optimization plot generated by RSM, the suggested optimal concentrations of yeast extract and CaCO3, as well as pH and incubation time for maximum bacteriocin production (80.2 AU/ml), were 13 g/l, 1.4 g/l, 7 and 24 hrs respectively. The results showed that bacteriocin was active for 30min at 20, 30 and 40˚C while 50% of its activity was lost at 50˚C. In addition, maximum bacteriocin activity was observed at pH 6 and 7 for 30min and disappeared completely at pH 4 and 9. Moreover, bacteriocin activity was completely lost after 90min of incubation with trypsin and pepsin which confirm its protein nature. Antimicrobial activity of bacteriocin was tested against 47 clinical isolates collected from patients suffering from different dental diseases. The results showed that the bacteriocin had an inhibitory activity against different isolates of S. mitis, S. mutans, S. oralis and Enterococcus.